NLRP3 inflammasome is a key driver of obesity-induced atrial arrhythmias. Issue 7 (1st February 2021) - Scott Jr, Larry; Fender, Anke C; Saljic, Arnela; Li, Luge; Chen, Xiaohui; Wang, Xiaolei; Linz, Dominik; Lang, Jilu; Hohl, Mathias; Twomey, Darragh; Pham, Thuy T; Diaz-Lankenau, Rodrigo; et al.
Abstract: Aims: Obesity, an established risk factor of atrial fibrillation (AF), is frequently associated with enhanced inflammatory response. However, whether inflammatory signaling is causally linked to AF pathogenesis in obesity remains elusive. We recently demonstrated that the constitutive activation of the 'NACHT, LRR, and PYD Domains-containing Protein 3' (NLRP3) inflammasome promotes AF susceptibility. In this study, we hypothesized that the NLRP3 inflammasome is a key driver of obesity-induced AF. Methods and results: Western blotting was performed to determine the level of NLRP3 inflammasome activation in atrial tissues of obese patients, sheep, and diet-induced obese (DIO) mice. The increased body weight in patients, sheep, and mice was associated with enhanced NLRP3-inflammasome activation. To determine whether NLRP3 contributes to the obesity-induced atrial arrhythmogenesis, wild-type (WT) and NLRP3 homozygous knockout (NLRP3 −/− ) mice were subjected to high-fat-diet (HFD) or normal chow (NC) for 10 weeks. Relative to NC-fed WT mice, HFD-fed WT mice were more susceptible to pacing-induced AF with longer AF duration. In contrast, HFD-fed NLRP3 −/− mice were resistant to pacing-induced AF. Optical mapping in DIO mice revealed an arrhythmogenic substrate characterized by abbreviated refractoriness and action potential duration (APD), two key determinants of reentry-promoting electrical remodeling. Upregulation of ultra-rapid delayed-rectifier K + -channel (Kv1.5) contributed to the shortening of atrial refractoriness. Increased profibrotic signaling and fibrosis along with abnormal Ca 2+ release from sarcoplasmic reticulum (SR) accompanied atrial arrhythmogenesis in DIO mice. Conversely, genetic ablation of Nlrp3 (NLRP3 −/− ) in HFD-fed mice prevented the increases in Kv1.5 and the evolution of electrical remodeling, the upregulation of profibrotic genes, and abnormal SR Ca 2+ release in DIO mice. Conclusion: These results demonstrate that the atrial NLRP3 inflammasome is a key driver of obesity-induced atrial arrhythmogenesis and establishes a mechanistic link between obesity-induced AF and NLRP3-inflammasome activation. Graphical Abstract: